Analysis of administrative and volumetric banking productivity An analytical study of a sample of Iraqi private banks for the period (2005-2020) - Al-Murshedi, Haider Jawad; Timuz, Sinar Sahib (Al-Ghary Journal of Economic and Administrative Sciences, 2024)
The Iraqi banking sector faces huge challenges resulting from intense competition in the banking environment and the failure to keep pace with developments taking place in the outside world. Banking productivity has become a preoccupation for many banks around the world, and perhaps the most prominent thing that helps these banks ensure their productivity is keeping pace with the developments witnessed by the external environment in which they operate and translating these developments into their internal environment. The study sample, and the results were obtained using (Data Envelopment Analysis) program based on the method of enclosing data for administrative productivity and volumetric, and data were collected from the annual financial reports of the Iraqi private banks listed in the Iraqi Stock Exchange and for a sample of (15) banks for a period of (2005) -2020), and the administrative and volumetric productivity analysis was adopted using the data envelope program, and a number of conclusions were reached, the most important of which is the presence of a discrepancy in the administrative and volumetric productivity of the banks in the study sample. Including it, the Iraqi private banks should improve the administrative and volumetric productivity, making them Achieving a new competitive advantage, reviving the national economy and gradually introducing it to the global financial markets, in order to achieve the required productivity and face the recurring financial crises in the Iraqi banking sector.